Comparative risk of anemia and related micronutrient deficiencies after Roux‐en‐Y gastric bypass and sleeve gastrectomy in patients with obesity: An updated meta‐analysis of randomized controlled trials. (19th January 2022) - Kwon, Yeongkeun; Ha, Jane; Lee, Yong‐Hoon; Kim, Dohyang; Lee, Chang Min; Kim, Jong‐Han; Park, Sungsoo
Summary: Although Roux‐en‐Y gastric bypass (RYGB) and sleeve gastrectomy (SG) are the most prevalent bariatric surgical procedures, high‐level evidence is scarce regarding the assessment of postoperative nutritional risk in RYGB versus SG. Therefore, we performed a systematic review and meta‐analysis to compare the risk of anemia and related micronutrient deficiencies after RYGB and SG. We analyzed 10 randomized controlled trials that compared RYGB and SG with reported incidence of postoperative anemia and/or anemia‐related micronutrient deficiencies (iron, vitamin B12, or folate). There were no significant differences in the risk of postoperative anemia (moderate level of evidence), iron deficiency (high level of evidence), or folate deficiency (moderate level of evidence). Patients undergoing RYGB had a higher risk of postoperative vitamin B12 deficiency than those undergoing SG (relative risk, 1.86; 95% confidence interval, 1.15–3.02; p  = 0.012; high level of evidence). Our findings imply that patients undergoing RYGB require more stringent vitamin B12 supplementation and surveillance than those undergoing SG. Additionally, our results may aid patients with high concern for anemia and related micronutrient deficiencies in making informed decisions regarding surgical methods based on nutritional risk.